2023
DOI: 10.3390/foods12163086
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Thermal Processing on the Composition of Curcuma longa Rhizome

Justyna Zagórska,
Wirginia Kukula-Koch,
Marcin Czop
et al.

Abstract: Curcuma longa L. (Zingiberaceae), known as turmeric, is a perennial tuberous plant from the genus Curcuma, which includes about 100 plant species. The chemical composition of the turmeric rhizome is very diverse. Diarylheptanoid derivatives, also known as curcuminoids (of which curcumin, demethoxycurcumin and bisdemethoxycurcumin are the most important representatives), are the major active constituents of the plant rhizome. Many extracts used in the food and pharmaceutical industries are produced from thermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…As can be seen from the obtained data, none of the samples showed a positive result for carotenoids. However, many studies have confirmed the high carotene content in turmeric [42], also red pepper is a rich source of bright representatives of carotenoids -lutein, carotene and capsanthin [43]. This indicates the inapplicability of this method of qualitative analysis to these extracts.…”
Section: Resultsmentioning
confidence: 99%
“…As can be seen from the obtained data, none of the samples showed a positive result for carotenoids. However, many studies have confirmed the high carotene content in turmeric [42], also red pepper is a rich source of bright representatives of carotenoids -lutein, carotene and capsanthin [43]. This indicates the inapplicability of this method of qualitative analysis to these extracts.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of the turmeric rhizome and its major active compounds, called curcuminoids, the boiling and frying process resulted in an increase in the content of these compounds (curcumin content: from 114 for the fresh rhizome to 204 mg/g after 10 min of boiling and to 224 mg/g after 10 min of frying). In the case of microwave heating, the trend was opposite-there was a decrease to 36 mg/g after 5 min [105]. The decrease in the antioxidant activity with an increase in temperature may result from ongoing processes and reactions leading to the formation of new substances with lower antioxidant activity compared to compounds present in the unprocessed raw material (for example, the formation of shogaols from gingerols in the case of ginger rhizome) [106].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the growing interest in the relationship between diet and health has elevated the importance of using spices in the food arena and understanding the mechanisms behind their beneficial properties [1]. Turmeric (Curcuma longa L.) is a perennial tuberous plant from the genus Curcuma (Zingiberaceae) and is commonly distributed in East, South, and Southeast Asia [2]. The rhizomes of turmeric are well-developed, clumped, branching, elliptic, or cylindrical and are widely used in many foods, such as canned beverages, baked products, dairy products, ice cream, yogurt, yellow cakes, milk, orange juice, biscuits, popcorn, cereals, sauces, and others, in the form of powder for over 4000 years [3,4].…”
Section: Introductionmentioning
confidence: 99%